Transcriptomic comparison of Drosophila snRNP biogenesis mutants reveals mutant-specific changes in pre-mRNA processing: implications for spinal muscular atrophy. - Garcia, E.L.; Wen, Y.; Praveen, K.; Matera, A.G. (RNA (New York, N.Y.), 2016)
Survival motor neuron (SMN) functions in the assembly of spliceosomal small nuclear ribonucleoproteins (snRNPs) that catalyze pre-mRNA splicing. Here, we used disruptions in Smn and two additional snRNP biogenesis genes, Phax and Ars2, to classify RNA processing differences as snRNP-dependent or gene-specific in Drosophila Phax and Smn mutants exhibited comparable reductions in snRNAs, and comparison of their transcriptomes uncovered shared sets of RNA processing changes. In contrast, Ars2 mutants displayed only small decreases in snRNA levels, and RNA processing changes in these mutants were generally distinct from those identified in Phax and Smn animals. Instead, RNA processing changes in Ars2 mutants support the known interaction of Ars2 protein with the cap-binding complex, as splicing changes showed a clear bias toward the first intron. Bypassing disruptions in snRNP biogenesis, direct knockdown of spliceosomal proteins caused similar changes in the splicing of snRNP-dependent events. However, these snRNP-dependent events were largely unaltered in three Smn mutants expressing missense mutations that were originally identified in human spinal muscular atrophy (SMA) patients. Hence, findings here clarify the contributions of Phax, Smn, and Ars2 to snRNP biogenesis in Drosophila, and loss-of-function mutants for these proteins reveal differences that help disentangle cause and effect in SMA model flies.